LEVEL OF ANXIETY RELATED TO ENGLISH LANGUAGE AMONG GENERAL NURSING AND MIDWIVES STUDENTS - K Deepak; Patel Dhara; Prajapati Preeti; Saini Kajal (Indian Journal of Psychiatric Nursing)
The present study was conducted to assess the level of anxiety related to English language among General Nursing & Midwives Students. A descriptive research design was adopted to assess the level of anxiety related to English language among General Nursing & Midwives Students in selected nursing schools. 40 students were selected by Simple Random sampling technique. The study revealed that the most of the students had intermediate level of anxiety.